PENGEMBANGAN PEMBELAJARAN BAHASA INDONESIA MELALUI E-LKPD BERBASIS LIVEWORKSHEET UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PESERTA DIDIK MADARASAH IBTIDAIYAH - Wiladhatin Ira Kusumawati; Rahmat Aziz; Mohamad Zubad Nurul Yaqin (Jurnal Manajemen Pendidikan, 2026)
This study aims to explore the development of Liveworksheet-based E-LKPD in Indonesian language learning that meets valid and effective criteria in improving student motivation and learning outcomes. This study uses a research and development (R&D) procedure with the ADDIE model. The subjects in this study were 30 second-grade students of Bahrul Ulum Bumiaji Elementary School. Data collection techniques used observation, interviews, documentation, questionnaires, and tests. The results of the study indicate that Liveworksheet-based E-LKPD development in the Indonesian Language subject obtained a criteria ratio of 98% for media validation, 95% for material validation and 93.9% for learning validation so that it is included in the very valid category. And the effectiveness of the Liveworksheet-based E-LKPD development in Indonesian Language learning has proven effective in increasing student motivation and learning outcomes. This is shown by the increase in posttest scores compared to pretests and a significance value of 0.000 <0.05. Thus, Liveworksheet-based E-LKPD is considered effective for use in learning because it is able to significantly increase student motivation and learning outcomes.